VISUAL PERCEPTION TOWARDS LANDSCAPE ELEMENTS IN PROMOTING RESTORATIVE ENVIRONMENTS: A CASE OF GAMUDA GARDEN, RAWANG - Muhammad Firdaus Juarsa; Nurul Akmaniza Mohd Nasir; Nawfal Kamarul Bahrain, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Rapid urbanisation led to decreasing rate of physical and mental health due to the hectic lifestyle living in a city. However, being in natural environment setting does provide a restorative experience for the visitors especially among urban community. It is very important to identify the landscape elements that stimulate brains and deliver relaxing situation to park visitors. This study employed a Q methodology to identify the landscape elements that successfully provide restorative environment setting for visitors in Gamuda Garden, Rawang, Malaysia. Photographs of five landscape elements that believed to provide restorative experience were captured and respondents were asked to rank order the photos according to its importance in providing restorative environment settings. The data collected were analysed using PQMethod software where factors were flagged, rotated and factor analysis were constructed. Four themes were generated which are tension relief, social value, natural value and comfort value. This study highlights the identification of landscape elements that provide restorative settings that should be taken into consideration in urban park planning and management.